2013 Annual Report Conference on Electrical Insulation and Dielectric Phenomena 2013
DOI: 10.1109/ceidp.2013.6748243
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of properties of electrical discharges developing in natural and synthetic ester at inception voltage

Abstract: This paper presents the results of the studies concerning propagation of the streamers in natural and synthetic ester under lightning impulse 1.2/50 μs at inception voltage. The results are presented in the form of comparison with the results obtained for mineral oil at the same conditions. For the different interelectrode gaps changed from 5 to 20 mm, the inception voltage and propagation velocity were measured and analyzed. Additionally, the oscillograms of light emitted during discharge development under in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…Other study at gap distance of 100 mm also showed the same pattern [17]. However, at small gap distances between 5 mm and 20 mm, it was found that the 50% breakdown voltages of vegetable oils at negative and positive polarities were quite close [20].…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Other study at gap distance of 100 mm also showed the same pattern [17]. However, at small gap distances between 5 mm and 20 mm, it was found that the 50% breakdown voltages of vegetable oils at negative and positive polarities were quite close [20].…”
Section: Introductionmentioning
confidence: 65%
“…In one of the study, it was reported that at gap distances between 5 mm and 20 mm, the 50% breakdown voltages of esters were quite close to Mineral Oil (MO) under both negative and positive polarities [20]. Other studies showed that the 50% breakdown voltages of vegetable oils were slightly lower than MO at gap distances between 60 mm and 100 mm [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that the kinematic viscosity of mineral oil was under the limit of IEC 60296 standard. Rozga et al [60] reported that the kinematic viscosity of mineral oil at 40°C also showed lower than the standard which is 9mm 2 /s. Other than that, Sun-Ho and Chang-Su [14] also reported low kinematic viscosity of mineral oil at 40°C which was 7.8mm2/s.…”
Section: Relative Permittivity (Dielectric Constant) Characteristicsmentioning
confidence: 99%
“…This cycle was related to previously estimated inception voltages of the streamers. A procedure of inception voltage estimation was described in detail in [28]. The calculations were performed using MOSTAT software where the maximum likelihood method was applied.…”
Section: Measurement Assumptionsmentioning
confidence: 99%